1976
DOI: 10.1042/bj1590563
|View full text |Cite
|
Sign up to set email alerts
|

A model for the kinetics of activation and catalysis of ribulose 1,5-bisphosphate carboxylase

Abstract: Further evidence for time-dependent interconversions between active and inactive states of ribulose 1,5-bisphosphate carboxylase is presented. It was found that ribulose bisphosphate oxygenase and ribulose bisphosphate carboxylase could be totally inactivated by excluding CO2 and Mg2+ during dialysis of the enzyme at 4 degrees C. When initially inactive enzyme was assayed, the rate of reaction continually increased with time, and the rate was inversely related to the ribulose bisphosphare concentration. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
142
2

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(160 citation statements)
references
References 22 publications
16
142
2
Order By: Relevance
“…This activation process is clearly distinguishable from the spontaneous in vitro activation process characterized previously (8,9) which is severely inhibited by preincubation with RuBP (3,6,8). The rubisco activation system also differs from the chloroplast ferredoxin-thioredoxin system, which catalyzes the activation of several photosynthetic enzymes by reduction with electrons derived from water (2), since rubisco activation proceeds in the presence of the artificial electron transport acceptors methylviologen (17) and pyocyanine.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This activation process is clearly distinguishable from the spontaneous in vitro activation process characterized previously (8,9) which is severely inhibited by preincubation with RuBP (3,6,8). The rubisco activation system also differs from the chloroplast ferredoxin-thioredoxin system, which catalyzes the activation of several photosynthetic enzymes by reduction with electrons derived from water (2), since rubisco activation proceeds in the presence of the artificial electron transport acceptors methylviologen (17) and pyocyanine.…”
Section: Discussionmentioning
confidence: 94%
“…The K,,t(CO2) of rubisco activation in the reconstituted system was 4 micromolar C02, compared to a K,A,(C02) of 25 to 30 micromolar CO2 for the previously reported spontaneous CO2/Mg2' activation mechanism. The activation process characterized here explains the high degree of rubisco activation at the physiological concentrations of 10 micromolar CO2 and 2 to 4 millimolar RuBP found in intact leaves, conditions which lead to almost complete deactivation of rubisco in vitro.The photosynthetic assimilation ofCO2 is initiated by rubisco.2 This enzyme exhibits complex regulatory properties, including a requirement that it be converted to an activated state in order to acquire catalytic competency (8,9,14). The activation of rubisco in vitro occurs by the spontaneous addition of activating CO2 (ACO2) to the e-amino group of a lysine residue near the active site, followed by the addition of Mg2' (Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme may also act as an internal monooxygenase and catalyze the oxygenolysis of RuBP, leading to the production of glycolic acid during photorespiration (reviewed [ 11). For maximum catalytic rates, the enzyme must first be activated by preincubation with a divalent cation and CO2 [2,3] and there is some evidence to suggest that the CO2 activation site is distinct from the catalytic site [4,5]. With regard to the divalent cation requirement of the eucaryotic enzyme, it has been shown that Mn*', Ni*' and Co*+ will substitute for Mg*+ for both carboxylase [6] and oxygenase [7] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the other substrate, RuBP, received little notice even though the early paper by Pon et al (1963) also showed that preincubation of the enzyme with RuBP led to reduced rates of activity. Later, a detailed analysis by Laing and Christeller (1976) provided evidence that RuBP was an inhibitor of activation, allowing them to extend the carbamylation model of Lorimer et al (1976). Finally, a paper by Jordan and Chollet (1983) most clearly showed that RuBP binding to the uncarbamylated enzyme resulted in a potent inhibition of the carbamylation/activation process.…”
mentioning
confidence: 99%